2022
DOI: 10.1002/mame.202200053
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Cyclic Olefin Copolymer Applications in Microfluidics and Microdevices

Abstract: Cyclic olefin copolymers (COC) are amorphous, transparent thermoplastics composed of cyclic olefin monomers (norbornene) and linear olefins (ethene). They are increasingly utilized as fabrication materials for microsystems and microfluidic devices, owing to their promising features of low water absorption, high electrical insulation, long-term stability of surface treatments, and resistance to a broad variety of acids and solvents. Many manufacturing processes for COC-based devices have been developed in recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 234 publications
0
28
1
Order By: Relevance
“…Therefore, we recommend replacing PC or glass bottles with quartz containers during in situ investigations. Since quartz bottles are relatively costly and fragile, bottles made of cyclic olefin copolymer (Agha et al 2022) or borosilicate glass (Cai et al 2017) are UV‐transparent and can be considered as an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we recommend replacing PC or glass bottles with quartz containers during in situ investigations. Since quartz bottles are relatively costly and fragile, bottles made of cyclic olefin copolymer (Agha et al 2022) or borosilicate glass (Cai et al 2017) are UV‐transparent and can be considered as an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclic olefin copolymers (COC) in particular, are a type of thermoplastic material composed of cyclic olefin monomers and linear olefins ( Bruijns et al, 2020 ; Agha et al, 2022 ). COC possesses numerous advantageous properties, including low water absorption, excellent electrical insulation, long-term surface treatment stability, and resistance to a broad range of acids and solvents ( Shakeri et al, 2022b ; Guan et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely to the previously reported works where the majority of microchannels were fabricated from glass or PDMS, other researchers explored polymer microfluidic fabrications via cheaper and simpler methods such as 3D printing and laser ablation [83].…”
Section: Organic Np Synthesismentioning
confidence: 99%
“…Alternative materials include polymers such as cyclic olefin copolymer (COC) and poly(methyl methacrylate) (PMMA). These thermoplastics are transparent and versatile, and can be used to fabricate microchannels via hot embossing, injection molding, micromachining, laser ablation, and 3D printing [83]. For example, Aranguren et al [156] fabricated PMMA serpentine microchannels via laser ablation, and demonstrated production of lipid NPs (188 nm) at a maximum flow rate of 5 mL/min.…”
Section: Future Direction Of Researchmentioning
confidence: 99%